Localized re-definition of legal justice: the feminine of the south in the early constitutional transition and its practice by the Consumer Protection Office of the MPDFT-Brasilia-Brazil - a framework for cross-border disputes in EC Consumer Law and policy - Oliveira, Lúcia Helena Barbosa de (The University of Edinburgh, 2009)
This thesis presents an alternative reading of law as a way to settle conflicts and dispense justice through the eyes of the feminine and their ethics of care as elaborated by Carol Gilligan. An elective articulation between cultural feminism and postmodern ethics has been defended rather than coincidence. It shows the aporias of modernity through the reading of postmodernity, especially the undeniable exigencies of Levinas’ ethics of alterity and the reading done by Derrida of Benjamin’s characterization of law as violence. The challenges of postmodernity in those respects remain and then the findings of Gilligan’s different voice are articulated to offer a possible Aufhebung . No coincidence is defended but a proper articulation is defended. This thesis defends a reconceptualisation of justice as a feminine virtue within a postmodern paradigm of law and its rematerialization and reflexiveness as well the advancement of Relational Contract Theory and Need- Oriented Contact Theory. It explores early practices of Consumer Protection Office of MPDFT-Brasilia-Brazil which were responding to a transition constitutional situation after the redemocratization of the country and were an institutional lost paradigm of justice as a feminine virtue. The desired outcome is to identify a possible framework for justice as care, considering a manifold diagnosed gap in consumer justice in the EC.
Keywords: conflict resolution; cultural feminism; Gilligan, Carol 1936-; justice; MPDFT-Brasilia-Brazil; justice as care